Dirt, Sweat, and Diesel : A Family Farm in the Twenty-first Century - Hilty, Steven L. (Book collections on Project MUSE., 2016)
"With fewer people engaged in agriculture today, it is no surprise that most Americans have little understanding of the challenges that modern farmers face. This book provides readers a glimpse into life on a modern Missouri farm where a variety of grains, grass seed, corn, and cattle are produced."--